Gene duplication and adaptive evolution of Toll-like receptor genes in birds. (June 2021) - Yang, Jiandong; Zhou, Ming; Zhong, Yun; Xu, Liqun; Zeng, Changjun; Zhao, Xiaoling; Zhang, Ming
Abstract: Toll-like receptors (TLRs) play an important role in innate immune through recognizes pathogens. In order to reveal the evolutionary patterns and adaptive evolution of avian TLRs, we examined 66 representative bird species in 26 orders. Phylogenetic results indicated that TLR1A and TLR1B may have differentiated functionally. Evolutionary analysis showed that the TLR genes in birds under strong Purification selection (0.165–0.4265). A total of 126 common positively selected codons were identified in 10 TLR genes of avian, and most sites were located in the extracellular leucine-rich repeat (LRR) functional domains, and both environment and feeding habits were external factors driving the evolution of avian TLR genes. Environmental pressures had a greater effect on TLR1B, TLR2B, TLR3 and TLR4, while feeding habits were active in affecting TLR2A, TLR2B, TLR15 and TLR21 . Our data suggested that TLR genes have been subjected to different selective pressures in the diversification of birds and that these changes enabled them to respond differently to pathogens from diverse sources. Highlights: The TLR genes have been subjected to strong purifying selection in birds. TLR1A and TLR1B may have differentiated functionally in birds. Both environmental pressures and feeding habits had affect the evolution of TLR genes in birds. A total of 126 common positively selected codons were identified, and most sites were located in the LRR functional domains.